Philosophy of Health Within the Metamodern Worldview Paradigm - Odynets O. (Futurity Research Publishing, 2024)
The issue of human health is one of the most pressing social crises facing humanity. This article reevaluated health as a manifestation of overall human well-being, drawing inspiration from the philosophical and anthropological principles of metamodernism. It involved identifying characteristics of anthropo-being during metamodernism, exploring changes in the philosophical understanding of "health" and "illness" across historical periods, and determining the influence of the metamodernist worldview on the "health-illness" system for forming human wholeness. Methods of historical analysis, structural analysis of the metamodern stage, and modelling, based on metamodern oscillation and the causal-systemic approach was used in the paper. The research results revealed that metamodernism features oscillations between opposites without negating either, forming a new quality of life based on synthesising previous intellectual traditions; seeking life's meaning by returning to individuality; and uniting spiritual and material modes of anthropo-being. The perception of "health" has shifted in accordance with the changing worldviews throughout history. In the era of metamodernism, merging opposing qualities to form harmony offers a fresh outlook on the "health-illness" dynamic, paving the way for personal development by transcending spiritual challenges and imperfections. This philosophical study of health through metamodernism highlighted illness's potential as an integral health system mode, stimulating individuality search, past experience transformation, and evolutionary spiritual growth. This approach offered new perspectives for revising contemporary medical paradigms, complementing treatment with psychological transformation practices. Metamodernist perspectives view the "health-illness" system as a fusion of the holistic health system's opposing elements. Illness is seen as a companion in the quest for deeper existential meaning. The oscillation of "health-illness" systems creates transformative flows, birthing new experiences, opening new life values and perspectives. This allows self-improvement and internal growth as individuals and parts of larger systems: collectives, society, and the planet. The result of internal spiritual growth consequently leads to physical healing.
Keywords: oscillations; holistic health; meaning of life; social health; health; illness; philosophy of medicine